UBL/BAG-domain co-chaperones cause cellular stress upon overexpression through constitutive activation of Hsf1 - Poulsen, Esben G. (Cell Stress Chaperones, 2016)
As a result of exposure to stress conditions, mutations, or defects during synthesis, cellular proteins are prone to misfold. To cope with such partially denatured proteins, cells mount a regulated transcriptional response involving the Hsf1 transcription factor, which drives the synthesis of molecular chaperones and other stress-relieving proteins. Here, we show that the fission yeast Schizosaccharomyces pombe orthologues of human BAG-1, Bag101, and Bag102, are Hsp70 co-chaperones that associate with 26S proteasomes. Only a subgroup of Hsp70-type chaperones, including Ssa1, Ssa2, and Sks2, binds Bag101 and Bag102 and key residues in the Hsp70 ATPase domains, required for interaction with Bag101 and Bag102, were identified. In humans, BAG-1 overexpression is typically observed in cancers. Overexpression of bag101 and bag102 in fission yeast leads to a strong growth defect caused by triggering Hsp70 to release and activate the Hsf1 transcription factor. Accordingly, the bag101-linked growth defect is alleviated in strains containing a reduced amount of Hsf1 but aggravated in hsp70 deletion strains. In conclusion, we propose that the fission yeast UBL/BAG proteins release Hsf1 from Hsp70, leading to constitutive Hsf1 activation and growth defects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-016-0751-z) contains supplementary material, which is available to authorized users.